First Methodist Church service - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a religious service at the First Methodist Church of San Jose. Two clergymen stand at a raised pulpit. To the left of the pulpit a choir is singing. The congregation stands below. On a table below the pulpit are several filled collection plates.